The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-87053-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in physicochemical parameters and microbial populations of mushrooms as influenced by nano-coating treatments

Abstract: White button mushrooms are greatly high perishable and can deteriorate within a few days after harvesting due to physicomechanical damage, respiration, microbial growth of the delicate epidermal structure. For that reason, the present research work was applied to evaluate the effect of chitosan combination with nano-coating treatments on physicochemical parameters and microbial populations on button mushrooms at chilling storage. Nano coating with the addition of nisin 1% (CHSSN/M) established the minimum valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
(34 reference statements)
3
12
0
Order By: Relevance
“…The chitosan biopolymer is commercially used in the food and pharmaceutical sectors due to its suitable physical, chemical and biological properties. It is biodegradable, nontoxic, and biofunctional, and it possesses biocompatible properties [12][13][14][15][16]. Edible films prepared with chitosan-based polymers have an excellent adhesiveness and cohesiveness with a smooth surface of food products [17].…”
Section: Introductionmentioning
confidence: 99%
“…The chitosan biopolymer is commercially used in the food and pharmaceutical sectors due to its suitable physical, chemical and biological properties. It is biodegradable, nontoxic, and biofunctional, and it possesses biocompatible properties [12][13][14][15][16]. Edible films prepared with chitosan-based polymers have an excellent adhesiveness and cohesiveness with a smooth surface of food products [17].…”
Section: Introductionmentioning
confidence: 99%
“…Succinate dehydrogenase activity (SDH) or respiratory Complex II is an enzyme complex, found in eukaryotes membrane or even inner mitochondrial cells. SDH enzyme activity was evaluated in cucumbers after changing the color from blue to colorless which depended on the sample enzymatic activity 33 , 34 . SDH enzyme activity was detected at an absorbance of 600 nm, remained linear for at least 3 min, and expressed as ∆OD per min −1 per mg protein −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The toughness of every treatment was evaluated using a texture profile unit (TPU-2S, Yamaden Co., Tokyo, Japan) with a 3 mm plunger moving at 150 mm min −1 . The crispness index was achieved from the force distance curves for the samples [32].…”
Section: Toughness Crispness Indexes Evaluationmentioning
confidence: 99%
“…Sugar is utilized as a substrate and energy source for respiratory metabolism. Zapotoczn and Markowski [32] reported that a higher sugar content meant a better quality was preserved of cucumber samples during storage.…”
Section: Sugar Analysismentioning
confidence: 99%